The judiciary and the bar (Civil) - Ali Mohamed, Ashgar Ali; Ali Tajuddin, Hanifah Haydar (CLJ Publication, 2020)
In light of the above, this chapter discusses the legal profession and practice in the civil courts in Malaysia. It begins by identifying the role and functions of judges, their appointments, conduct and etiquette; and the qualifications and requirements for admission to the Bar in Malaysia as an Advocate and Solicitor. Further, the discussion encompasses the bodies that regulate professional practice and etiquette in Malaysia such as the disciplinary board, the Bar Council and the State Bar Committee. The discussion will also encompass the functions of the Legal Profession Qualifying Board Malaysia.